The spatial distribution of asbestos and the community awareness and perception of asbestosis risk in Ga-Mathabatha, Limpopo Province, South Africa - Thobejane, Manuel Teleki (My University, 2025)
Asbestos dust exposure poses a significant public health concern, particularly in areas characterised by unrehabilitated asbestos mines. As such, this study aims to evaluate the spatial distribution of asbestos and the community awareness and perception of the risk of asbestosis in Ga-Mathabatha. Remote sensing analysis techniques were adopted to predict areas containing different types of minerals associated with asbestos. Meanwhile, field observations were carried out to validate the presence of asbestos in such areas. Patterns and trends in wind speed and direction - factors critical to asbestos minerals distribution - were analyzed and their potential influence was described. Furthermore, 18 in-depth interviews and 250 survey questionnaires were administered as part of a mixed-methods design for evaluating the community's awareness and perception of asbestosis risk. Remote sensing analysis results predicted that chrysotile asbestos was highly concentrated in the eastern part of the community, meanwhile tremolite asbestos dominated the southern part, and a few of the serpentine in the eastern part. Evidence from field observations concurs with these findings, revealing that asbestos deposits are present in the surrounding villages and along riverbanks. Meteorological data has shown that the asbestos dumping sites lie within the path of dominant winds, suggesting a potential risk of windborne asbestos fiber dispersion into surrounding areas. Conversely, survey results revealed that 66% of participants were aware of the danger of exposure to asbestos dust, while 40.8% (32.8% + 8%) perceived asbestosis as deadly and incurable. The results underscore the importance of education and awareness programs targeting individuals with limited knowledge and negative perceptions, and those engaging in activities that increase their exposure.
Thesis (M.Sc. (Geography and Environment Science)) -- University of Limpopo, 2025
Keywords: Asbestos dust exposure; Asbestosis; Distribution; Ga-Mathabatha community; knowledge; Awareness; Practice; Perception; Asbestos dust; Asbestosis; Asbestos mines and mining